Pendampingan Pengelolaan Arsip Data Pensiun dan Pelayanan Taspen Malang - Muhammad Syafriel; Novy Karmelita Indrawati; Anis Dwiastanti; Yudhi Anggoro (Lembaga Pengembangan Kinerja Dosen, 2025)
PT. Taspen is engaged in the field of Pension Insurance and Old Age Benefits with financial management and reliable services as well as quality insurance products. The purpose of this service is to assist the pension archive management process at Malang Branch. This service is descriptive using observation, interviews, documentation and literature studies. The analysis uses literature studies and direct observations in the field. Administrative activities in the service division are managing, receiving, producing and storing files into archives. Pension archive management plays an important role so that it must be in accordance with established procedures. Pension archives consist of submissions of pension participant rights claims that are stored so as to determine the smoothness of the service process for pension participants. The more files that are collected and stored, the more important archive management is in its role as a source of information that is orderly and neat, making the tasks of the service section for pension participants able to run smoothly and on time. The result of the service is a pension archive management system including receiving archives in the form of file sorting, sorting archive numbers, sterilizing archives, weeding files, scanning, Compressing and ELO (Electronic Leitz Ordner), and storing archives. The storage of archives is carried out by arranging the file boxes on the archive rack according to the archive number listed on the map. The activities of borrowing and rediscovering archives are carried out according to the archive number needed in the participant service process. And another activity is the destruction of pension archives carried out by the general section if they are no longer needed.